Ad libitum and restricted day and night sleep architecture. (2nd January 2016) - Korompeli, Anna St; Muurlink, Olav; Gavala, Alexandra; Myrianthefs, Pavlos; Fildissis, Georgios; Baltopoulos, Georgios
ABSTRACT: This study represents a first controlled comparison of restricted versus unrestricted sleep in both day and night sleep categories. A repeated measures study of a homogenous group of young women without sleep disorders ( n =14) found that stage 1, 2, 3 and REM sleep, as well as sleep latency were not statistically different between day ad libitum sleep (DAL) and day interrupted (DI) sleep categories, while night interrupted (NI) and ad libitum (NAL) sleep showed strikingly different architecture.